Peer relationships in cultural context - Chen, Xinyin; French, Doran C.; Schneider, Barry H. (Cambridge ; New York : Cambridge University Press, 2006)
"This edited volume responds to the absence of a comprehensive consideration of the implications of culture for children's peer relationships. Although research in this field has burgeoned in recent years, cultural issues have often been overlooked. The chapters in this book tap such issues as the impact of social circumstances and cultural values on peer relationships, culturally prescribed socialization patterns and processes, emotional experience and regulation in peer interactions, children's social behaviors, cultural aspects of friendships, and peer influences on social and school adjustment in cultural context. The role of culture and development is particularly emphasized in the chapters. The authors incorporate into their discussions findings from research programs using multiple methodologies, including both qualitative (e.g., interviewing, ethnographic, and observational) and quantitative (e.g., large-scale survey, standardized questionnaire) approaches, based on a wide range of ages (from early childhood to youth) of children in cultures from East to West and from South to North (Asia, South America, the Mid East, Southern Europe, and ethnic groups in the United States)."--Publisher's description
Culture and peer relationships / Xinyin Chen, Doran C. French, Barry H. Schneider -- Children's social behaviors and peer interactions in diverse cultures / Carolyn Pope Edwards [and others] -- Cultural influences on peer relations : an ecological perspective / Anne Marie Tietjen -- Analytic considerations in cross-cultural research on peer relations / Noel A. Card, Todd D. Little -- Qualitative research on children's peer relations in cultural context / William A. Corsaro -- Temperament, socioemotional functioning, and peer relationships in Chinese and North American children / Xinyin Chen, Li Wang, Amanda DeSouza -- Emotional aspects of peer relations among children in rural Nepal / Pamela M. Cole, Alisha R. Walker, Mukta S. Lama-Tamang -- Emotion, emotion-related regulation, and social functioning / Nancy Eisenberg [and others] -- Temperamental and emotional influences on peer relationships / Joan Stevenson-Hinde -- Parenting and peer-group behavior in cultural context / David A. Nelson [and others] -- Real and symbolic entry of children in the social world of peers and parent--child interactions : cultural and cross-cultural aspects / Paul P. Goudena -- Culture, family contexts, and children's coping strategies in peer interactions / Yiyuan Xu [and others] -- The cultural organization of Yucatec Mayan children's social interactions / Suzanne Gaskins -- Cross-cultural differences in competition among children and adolescents / Barry H. Schneider [and others] -- Ethnic peer discrimination and psychological well-being among early adolescents / Maykel Verkuyten -- On hand-holding, spit, and the "big tickets" : a commentary on research from a cultural perspective / Kenneth H. Rubin -- Friendships of Indonesian, South Korean, and U.S. Youth : exclusivity, intimacy, enhancement of worth, and conflict / Doran C. French, Okhwa Lee, Sri Untari Pidada -- The cultural practice of close friendships among urban adolescents in the United States / Niobe Way -- Latino-Heritage adolescents' friendships / Margarita Azmitia, Angela Ittel, Charlotte Brenk -- The Cultural context of children and adolescents : peer relationships and intimate friendships among Arab and Jewish children in Israel / Ruth Sharabany -- Peers and culture : details, local knowledge, and essentials / William M. Bukowski, Ryan Adams -- Peer relationships in cultural perspective : methodological reflections / Barry H. Schneider, Doran C. French, Xinyin Chen.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Interpersonal relations in children; Social interaction in children; Culture -- Psychological aspects; Children; Socialization; Cross-cultural studies; Interpersonal Relations; Child; Peer Group; Socialization; Cross-Cultural Comparison; Relations humaines chez l'enfant.; Interaction sociale chez l'enfant.; Culture -- Aspect psychologique; Enfants; Socialisation; Études transculturelles; Enfance; children (people by age group); childhood; FAMILY & RELATIONSHIPS -- Friendship; Socialization; Cross-cultural studies; Children; Culture -- Psychological aspects; Interpersonal relations in children; Social interaction in children; Peer-Group; Interaktion; Interpersoonlijke relaties; Kinderen; Culturele invloeden; dissertations; Academic theses; Academic theses; Thèses et écrits académiques.